APPLICATION OF RICE HUSK AND CHICKEN MANURE TO THE GROWTH AND PRODUCTION OF Red Spinach (Amaranthus gangeticus L.) - CIK ZULIA; SYAHMINAR BATUBARA (CV KULTURA DIGITAL MEDIA, 2020)
The research was conducted in Kisaran Naga Village, Kisaran Timur District, Asahan Regency, with a flat topography and a height of ± 15 m above sea level, ± 2 km from the Faculty of Agriculture, Asahan University, and climate classification according to Oldeman, Asahan Regency, including climate type E1 with wet months> 200 mm namely in September, October, and November. and dry months <100 mm were only found in February. This research was conducted from March to April 2014.This research was prepared based on a factorial randomized block design (RBD) with 2 treatment factors and 3 replications. The first factor is the provision of rice husk ash with 3 levels, namely: S0 = without fertilizer, S1 = 2 kg / plot, S2 = 4 kg / plot and S3 = 6 kg / plot. The second factor is the provision of chicken coop fertilizer with 4 levels, namely A0 = 0 kg / plot, A1 = 1 kg / plot, A2 = 2 kg / plot and A3 = 3 kg / plot. The results of the study were giving the best rice husk ash on treatment S0 (0 kg / plot) to the highest plant height at 3 weeks after planting, namely 20.25 cm, the best number of leaves in S2 treatment was 12.64 strands, the best production per plant sample in treatment S3 is 356.88 g, and the best production per plot in S2 treatment is 1.64 kg when compared to without treatment of rice husk ash fertilizer, which is 1.23 kg. Giving the best chicken manure on A3 treatment (3 kg / plot) to the highest plant height at 3 weeks after planting was 21.11 cm, the best number of leaves was 12.76 strands and the production per plot was 1.63 kg when compared to without The treatment of rice husk ash fertilizer was 1.38 kg, while the best sample production per plant was 347.50 g and the interaction of treatment of rice husk ash and chicken manure on the growth and production of red spinach showed no significant effect. against all observed parameters.